Financial literacy for SMEs in Yogyakarta after a decade of SMEs Act - Yaya, Rizal; Setiartiti, Lilies; Darsono, Susilo Nur Aji Coko; Akhbar, Taufik; Mohd Alwi, Norhayati (UMY Press, 2020)
The purpose of this chapter is to assess the level of financial literacy for the MSMEs in Yogyakarta after a decade of the issuance of Act 20-year 2008 on Micro, Small and Medium Enterprises. Data were obtained from survey-ing 301 MSMEs in Yogyakarta. The results indicated that most of MSMEs have never used financial statements and accounting information in making decisions related to their business development and consider that account-ing information is not important for their business. Overall, this chapter pro-vides some important insights into Yogyakarta to highlight possible steps for the policy makers as a reference to formulate policies related to increasing financial literacy for MSMEs.